Talking Points: The Likely Economic Consequences from Raising New York's Cigarette Excise Tax by $0.55 Per Pack (Tufts Archival Research Center, 2007)
Philip Morris talking points on the likely economic consequences of an increase in New York's cigarette excise tax. Includes charts on job and sales losses. Explores likely cigarette tax increases in other states if such a tax increase is passed in New York. Questions effect of such a tax on the existing revenue base and the reliability of the tax.